Accuracy of Oral Liquid Measuring Devices Used Among Caregivers at Hospital Dungun - Nuraina Mohd Norizan; Erma Atika Laere; Nurul Ain Sarmo (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
Oral liquid medications are common type of dosage form prescribed to children. Caregiver responsible to choose appropriate measuring device to measure intended dose and minimize dosing error. Objectives of this study were 1) To identify types of measuring devices used at home; 2) To determine dose error deviation across all the measuring devices. This cross-sectional study involved caregivers visiting outpatient pharmacy with oral liquid prescription that fulfilled inclusion and exclusion criteria. The caregivers were instructed to measure 4.8ml and 15.0ml liquid by using suitable devices provided, which were 4 types of syringes and 2 types of dosing cups. The measured liquid was read by investigator and any dose error deviation was calculated and reported as percentages. Data was analyzed descriptively using SPSS version 21. Out of 120 caregivers involved, 60% were female (n=72), aged between 31-40 years old (49.1%, n=59), and employed (62.5%, n=75). 82 caregivers (68.3%) received secondary education level. Most caregivers use standardized measuring devices at home, particularly syringes and dosing cups. For smaller dose, less dose error was detected if using syringe (13.3%) as compared to dosing cup (39.3%); while for larger dose, both syringe and dosing cups are acceptable (11.7% and 7.4% respectively). Syringe shows less dose error as compared to dosing cup for smaller dose. Pharmacist should participate in decision making of choosing right measuring device to improve accuracy of medication administration.